Problem-based learning in mathematics learning to improve reflective thinking skills and self-regulated learning - Yuni, Yatha; Kusuma, Arie Purwa; Huda, Nurul (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research was aimed to determine the effectiveness of the Problem-Based Learning (PBL) model in mathematics learning on students' reflective thinking skills and self-regulated learning. The researchers employed the quantitative-qualitative method. The quantitative data was obtained through pretest and posttest, and qualitative data were obtained through interviews with three students selected using a purposive random sampling technique. The research subjects were selected using the accidental sampling technique because it was still in the new normal era of the COVID-19 pandemic. The subjects consisted of 33 eighth-grade students. The data was collected using test instruments and questionnaires. Furthermore, the data was tested using the independent sample t-test. This research found three results. First, there was a significant increase in reflective and self-regulated thinking skills through the application of the PBL model. Second, based on the t-test, there was a reflective thinking skills difference between pretest and posttest, with a higher score was found in the posttest. Third, there was no self-regulated learning difference between the pretest and posttest.